2015
DOI: 10.1631/jzus.b1400355
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of two methods for miRNA isolation from milk whey

Abstract: MicroRNAs (miRNAs) from milk whey have been considered for their potential as noninvasive biomarkers for milk quality control and disease diagnosis. However, standard protocols for miRNA isolation and quantification from milk whey are not well established. The objective of this study was to compare two methods for the isolation of miRNAs from milk whey. These two methods were modified phenol-based technique (Trizol LS ® followed by phenol precipitation, the TP method) and combined phenol and column-based appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…We found that the TLS protocol is best suited for extracting RNA from bovine MDEs isolated with EQ and DUC methods ( Fig 8 ). This supports previous studies that have isolated high quality RNA suitable for high throughput sequencing from bovine MDEs using the Trizol LS protocol described herein [ 78 , 79 ]. Moreover, minimal differences in RNA yield and/or purity across TLS, Tri + RCC, and TLS + RCC protocols were found for human MDEs isolated via EQ ( Fig 11 ), suggesting that the three methods can be used to isolate good quality RNA from human EQ MDEs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the TLS protocol is best suited for extracting RNA from bovine MDEs isolated with EQ and DUC methods ( Fig 8 ). This supports previous studies that have isolated high quality RNA suitable for high throughput sequencing from bovine MDEs using the Trizol LS protocol described herein [ 78 , 79 ]. Moreover, minimal differences in RNA yield and/or purity across TLS, Tri + RCC, and TLS + RCC protocols were found for human MDEs isolated via EQ ( Fig 11 ), suggesting that the three methods can be used to isolate good quality RNA from human EQ MDEs.…”
Section: Discussionsupporting
confidence: 89%
“…Since the identification of RNA in exosomes in 2007 [ 20 ], numerous extraction methods have been used for exosome RNA profiling, including real time quantitative PCR (RT-qPCR), microarrays, and RNA sequencing. However, enrichment and molecular profiling of MDEs remain technically challenging [ 47 ] due to the variability in RNA extraction protocols and commercially available RNA extraction kits that are often utilized in EV research [ 56 58 ]. Here, we tested four MDE-based RNA extraction protocols: three commercially available kits 1) QIAzol + miRNeasy Mini Kit (Q), 2) TRIzol + RNA Clean and Concentrator Kit (Tri+RCC), 3) TRIzol LS + RCC (TLS+RCC) and an inhouse phenol-based extraction method, 4) TRIzol LS (TLS) [ 59 ], to identify a reproducible and optimal RNA extraction method that can be used to isolate high quality RNA (≥17 nucleotides) from bovine and human MDEs.…”
Section: Introductionmentioning
confidence: 99%
“…Historical and recent literature provides robust data that support this range [ 6 , 7 ]. For instance, comprehensive reviews and case series analyses, which collectively examined hundreds of lymphoma cases, have found that composite lymphomas - those involving both Hodgkin and non-Hodgkin components - comprise a minor fraction of lymphoma diagnoses, solidifying their status as a rare clinical entity [ 8 ]. We report a rare case of composite lymphoma featuring both classical Hodgkin and Burkitt lymphoma within a single patient.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have employed bioinformatic approaches to analyze HBM-derived exosome compositions and discovered various disease biomarkers [ 19 , 20 , 21 , 22 , 23 , 24 ]. However, no comprehensive research has examined bioactive HBM-derived exosome factors for their immune-related and antimicrobial properties through transcriptomic and proteomic studies by utilizing multiple databases to analyze and predict their biological function.…”
Section: Introductionmentioning
confidence: 99%